Candlelight demonstrations and the presidential impeachment in South Korea: An evaluation of the 30 years of democracy. Issue 3 (8th July 2019) - Kang, Shin-Goo
Abstract : Purpose: The purpose of this paper is to introduce and analyze the short-term and long-term causes of the candlelight demonstrations and the ensuing presidential impeachment in South Korea, as well as the characteristics of the organization that planned the candlelight demonstrations and the participants of them. Design/methodology/approach: The research is based on the previous literature, news articles, as well as various surveys on the randomly selected participants of the demonstrations and on a representative sample of Korean electorate, including non-participants as well. Findings: The candlelight demonstrations, although "triggered" by a news report, would not have occurred, without angers and discontents accumulated over the president's whole term by the irregularities and wrongdoings of the administration. The system of checks and balances in democratic system did not work properly. In that regard, the candlelight demonstrations and the ensuing presidential impeachment were just an unanticipated expression of the problems and defects built in the Korean democratic system of 1987, which would have found a way out in any form eventually. Originality/value: Based on the analysis of the candlelight demonstrations and the ensuing presidential impeachment, the paper suggests instructive implications on a new democracy as well as on modern representative democracies that are in jeopardy now.